A low-expansion high-strength magnesium-aluminum-silicon glass composite ceramic substrate and a preparation method thereof

CN122958066APending Publication Date: 2026-10-23NO 43 INST OF CHINA ELECTRONICS TECH GRP CETC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610943799.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

镁铝硅系玻璃体系以MgO–Al2O3–SiO2为主体网络,具有可调微晶化行为和良好的热稳定性,但其在高强度低膨胀封装基板中的应用仍缺乏系统研究

Benefits of technology

本发明通过镁铝硅系玻璃与堇青石、锂辉石及微量氧化铝陶瓷填料的协同复配,在基板内部构建了低膨胀晶相网络与高强度增强结构共存的复合体系。该体系在低温共烧条件下即可实现致密化,使基板兼具良好的热膨胀特性,以及优异的抗弯强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958066A_ABST
    Figure CN122958066A_ABST
Patent Text Reader

Abstract

The application discloses a low-expansion high-strength magnesium-aluminum-silicon glass composite ceramic substrate and a preparation method thereof. The raw material of the green tape of the glass composite ceramic substrate comprises glass powder and ceramic filler, and the mass ratio of the glass powder to the ceramic filler is 20-75:25-80; the ceramic filler is composed of alumina, cordierite and spodumene. The low-expansion crystal phase network and the high-strength reinforced structure coexist in the substrate through the synergistic compounding of the magnesium-aluminum-silicon glass, the cordierite, the spodumene and the trace alumina ceramic filler. The system can realize densification under the low-temperature co-firing condition, and the substrate has good thermal expansion characteristics and excellent bending strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic packaging ceramic materials technology, specifically a low-expansion-coefficient, high-strength magnesium-aluminum-silicon glass composite ceramic substrate and its preparation method. Background Technology

[0002] With the rapid development of artificial intelligence chips, third-generation semiconductor devices, and high-power-density electronic modules, packaging substrates must withstand significant thermal cycling and mechanical loads during service. Mismatch between the thermal expansion coefficient of the substrate material and the chip will cause interfacial thermal stress concentration, severely affecting device reliability. While existing alumina ceramics possess high strength, their thermal expansion coefficient is relatively high; low-expansion ceramics such as spodumene suffer from difficulties in densification, high sintering temperatures, or insufficient mechanical properties. Glass-ceramic composite systems have become an important development direction for low-expansion substrate materials because they can fill ceramic grain boundaries with glass phases, lower sintering temperatures, and regulate thermal expansion behavior. Magnesium-aluminum-silicon glass systems, with MgO–Al2O3–SiO2 as the main network, exhibit tunable microcrystallization behavior and good thermal stability, but their application in high-strength, low-expansion packaging substrates still lacks systematic research. Therefore, it is necessary to develop a low-expansion, high-strength glass-ceramic composite substrate material based on magnesium-aluminum-silicon glass and its preparation method. Summary of the Invention

[0003] In view of this, the present invention provides a low-expansion-coefficient, high-strength magnesium-aluminum-silicon glass composite ceramic substrate and its preparation method. By synergistically combining specific glass with ternary ceramic fillers, the substrate achieves low thermal expansion characteristics that are well thermally matched with semiconductor chips, while significantly improving the mechanical strength of the substrate. This effectively solves the technical contradiction between insufficient strength of low-expansion materials and expansion mismatch of high-strength materials.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention discloses a low-expansion-coefficient, high-strength magnesium-aluminum-silicon glass-ceramic composite substrate, comprising a composite ceramic raw material tape and a noble metal conductor film printed on the composite ceramic raw material tape; the raw materials of the composite ceramic raw material tape include glass powder and ceramic filler; the mass ratio of the glass powder to the ceramic filler is 34-55:25-80; the ceramic filler is composed of alumina, cordierite, and spodumene.

[0005] This invention discovers that the relationship between magnesium aluminum silicon glass and cordierite-spodumene-alumina ternary ceramic filler with a specific composition is not a simple physical mixing and sintering fluxing relationship, but rather exhibits significant chemical compatibility and synergistic crystallization behavior.

[0006] During the low-temperature co-firing process, the Mg in the magnesium-aluminum-silicon glass... 2+ Al 3+ and Si 4+Plasma, in its molten state, possesses suitable migration activity, enabling it to undergo interfacial localized mutual dissolution with the surface lattices of cordierite (2MgO·2Al2O3·5SiO2) and spodumene (Li2O·Al2O3·4SiO2) fillers, forming a liquid / solid phase reaction layer with a transitional composition. This reaction layer lowers the overall free energy of the system during the subsequent heat treatment stage, inducing heterogeneous nucleation and directional crystallization of the glassy phase on the surface of cordierite and spodumene grains. This results in the in-situ precipitation of microcrystalline phases isomorphic to or thermally expanding with cordierite and spodumene. This crystallization not only enhances the microcrystallization of the glassy phase itself but also constructs a continuous network framework dominated by low-expansion crystalline phases between the filler grains.

[0007] In contrast, if other low-melting-point glass systems (such as borosilicate glass, zinc borosilicate glass, or yttrium telluride glass) are used to replace the magnesium aluminum silicon glass of this invention, the glass composition lacks ionic radii and coordination field environments that match the lattice of cordierite and spodumene, making it difficult to form an effective induced crystallization layer at the interface. Such mismatched glasses may only act as inert fluxes during sintering and fail to participate in crystallization, or they may precipitate heterocrystalline phases such as cristobalite and gahnite with high thermal expansion coefficients or phase transformation stresses due to interfacial reaction mismatch, thereby disrupting the low-expansion network of the filler and leading to an increase in the thermal expansion coefficient or deterioration of the substrate's mechanical properties.

[0008] Therefore, the technical effect of this invention comes from the specific chemical compatibility between the magnesium aluminum silicon glass component and the cordierite-spodumene-alumina ceramic filler. The two together constitute the core inventive concept of this invention and cannot be separated or arbitrarily replaced.

[0009] As a further aspect of the present invention: the glass powder is prepared from the following raw materials in the following mass percentages: SiO2 45%~55%; Al2O3 12%~19%; MgO 9%~15%; B2O3 12~15%; Li2O 3%~7%; ZnO 0~6%; La2O3 or Y2O3 0.3%~5%.

[0010] As a further embodiment of the present invention: the mass of alumina accounts for 2.9% to 5.2% of the total mass of the ceramic filler, the mass of cordierite accounts for 30.9% to 49.0% of the total mass of the ceramic filler, and the mass of spodumene accounts for 11.2% to 15.2% of the total mass of the ceramic filler.

[0011] As a further aspect of the present invention, the raw material tape further includes an organic casting system, wherein the amount of the organic casting system added is 77% to 85% of the total mass of the glass powder and ceramic filler.

[0012] As a further aspect of the present invention: the organic casting system comprises at least one of a dual-solvent system, a dispersant, a binder, and a plasticizer.

[0013] As a further aspect of the present invention: the dual solvent system is composed of ethanol and isopropanol in a mass ratio of 1:(1.2 to 1.6).

[0014] As a further aspect of the present invention: the dispersant is selected from castor oil, polyacrylamide, or a combination thereof; the binder is polyvinyl butyral; and the plasticizer is dibutyl phthalate or its equivalent.

[0015] As a further aspect of the present invention, the mass ratio of the dual solvent system, dispersant, binder and plasticizer is (40-70): (3-8): (6-18): (6-15).

[0016] As a further aspect of the present invention, its average coefficient of thermal expansion in the range of room temperature to 400°C is 3.0 to 3.6 ppm / K, and its flexural strength is ≥260 MPa.

[0017] Secondly, the present invention discloses a method for preparing the composite ceramic substrate as described above, comprising the following steps: The glass powder is obtained by melting, quenching, crushing, and grinding the raw materials. The glass powder is mixed with ceramic filler and organic casting system to form a slurry, which is then cast, stacked, and printed with precious metal conductors to obtain a multi-layer green body. The multilayer green body is co-fired at 850~950℃ to obtain the low-expansion coefficient, high-strength magnesium-aluminum-silicon glass composite ceramic substrate.

[0018] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes a synergistic blend of magnesium aluminum silicon glass with cordierite, spodumene, and trace amounts of alumina ceramic fillers to construct a composite system within a substrate that combines a low-expansion crystalline network with a high-strength reinforcing structure. This system can achieve densification under low-temperature co-firing conditions, giving the substrate both excellent thermal expansion characteristics and superior flexural strength.

[0019] This invention overcomes the technical bottlenecks of traditional low-expansion ceramic materials, such as difficulty in densification and insufficient mechanical properties, and high-strength ceramic materials with high coefficients of thermal expansion. It effectively reduces the risk of warpage and thermal stress failure of the package during thermal cycling, providing a substrate solution with both thermal compatibility and structural stability for the field of high-reliability electronic packaging. Attached Figure Description

[0020] Figure 1 This is a microstructure diagram of the surface of a low-expansion-coefficient, high-strength magnesium-aluminum-silicon glass composite ceramic substrate after sintering the A1 formulation of Example 1 of the present invention at 930°C. This microstructure achieves a perfect balance between high strength and low expansion coefficient through the dense matrix and the dispersion strengthening of hard particles, resulting in both a low thermal expansion coefficient and high mechanical strength. Detailed Implementation

[0021] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0023] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional methods in the prior art, and therefore will not be described in detail; unless otherwise specified, the parts in the following embodiments refer to parts by weight.

[0024] The following examples and comparative examples were prepared according to the following methods: (1) Preparation of glass powder Weigh each component according to the proportions in Table 1, and ball mill for 18 hours to obtain a uniformly mixed raw material. Place the raw material in a platinum crucible, and place the crucible in a muffle furnace. Heat the muffle furnace to 1550℃ and hold for 2-3 hours to allow the raw material to fully melt and react, thereby obtaining a uniform glass melt. The glass melt was quickly poured into deionized water for water quenching to obtain glass fragments. The glass fragments are crushed in a roller mill to obtain coarsely ground glass powder. The coarsely ground glass powder is then put into a ball mill and milled for 5 hours at a ball:water:material ratio of 5:2:1, using distilled water, to obtain a uniform slurry. The slurry is placed in a vacuum drying oven and dried at 80-100℃ for 4-6 hours to remove moisture. Finally, it is passed through a 2000-mesh sieve to obtain glass powder with a particle size of 2-3μm, which is then ready for use.

[0025] Table 1. Proportions of each component in the glass system

[0026] (2) Preparation of raw material tape and substrate processing According to the formula listed in Table 2, weigh out magnesium aluminum silicon glass powder and ceramic filler (composite powder of cordierite, spodumene and alumina), and add them to the organic casting system by means of external addition. Add the mixed materials to the ball mill jar and ball mill for 6 hours to obtain a uniformly dispersed casting slurry. After vacuum degassing treatment, cast the slurry through a casting machine, control the casting speed and doctor blade height to make the wet film thickness uniform, and then dry it naturally at room temperature or at low temperature to obtain a magnesium aluminum silicon glass composite ceramic raw material tape with a thickness of 124μm.

[0027] The dried raw material tape is cut, and the multiple layers of raw material tape are aligned and stacked in the stacking order. They are then placed in a warm isostatic press and laminated at 65°C and 3000psi to ensure that the layers are tightly bonded. Finally, they are cut into single-element blanks for individual substrates.

[0028] The green blank was placed in a sintering furnace and co-fired using a segmented heating process: first, the temperature was raised to 520℃ at a rate of 2℃ / min and held for 3 hours to allow the organic tapered system to fully decompose and dissipate; then, the temperature was further raised to the sintering temperature shown in Table 3 at a rate of 5~10℃ / min and held for 90 minutes to allow the glass phase to melt and spread and the ceramic phase to sinter densely, completing the low-temperature co-firing; after cooling to room temperature in the furnace, a low-expansion coefficient, high-strength magnesium-aluminum-silicon glass composite ceramic substrate was obtained. Performance tests were performed on the sintered samples, and the results are summarized in Table 3.

[0029] Table 2

[0030] In Table 2, the solvent is a mixture of ethanol and isopropanol in a mass ratio of 1:1.4; the dispersant is a mixture of castor oil and polyacrylamide in a mass ratio of 1:1; the binder is polyvinyl butyral; and the plasticizer is dibutyl phthalate.

[0031] Table 3

[0032] The test methods in Table 3 are as follows: Thermal expansion coefficient test: Refer to GB / T 5594.3-1985 "Test methods for performance of structural ceramic materials for electronic components - Part 3: Test method for average linear expansion coefficient", use a thermal expansion meter, test temperature range from room temperature to 400℃, heating rate of 5℃ / min, and calculate the average linear expansion coefficient.

[0033] Bending strength test: Refer to GB / T 6569-2006 "Test method for bending strength of fine ceramics", adopt the three-point bending method, the sample span is 30mm, and the loading rate is 0.5mm / min.

[0034] Dielectric performance testing: Referring to GB / T 5594.4-2015 "Test methods for the performance of structural ceramic materials for electronic components - Part 4: Test method for dielectric constant and dielectric loss tangent", the dielectric constant and dielectric loss were tested at a frequency of 1MHz using impedance analysis, and the test environment temperature was 23±2℃.

[0035] As can be seen from the experimental results in Table 3, the coefficient of thermal expansion and flexural strength of all formulations in Comparative Example 1 are significantly worse than those of formulation A3 in Example 1. This indicates that under the same magnesium-aluminum-silicon glass system, once the ratio of cordierite / spodumene / alumina ternary ceramic filler deviates from the range defined by this invention, especially when the spodumene content is less than 15% (7% in E2 and 8.5% in E3), the precipitation and network construction of the low-expansion crystalline phase will be severely damaged, leading to a sharp increase in the coefficient of thermal expansion and a sharp drop in strength. The results of Comparative Example 2 further confirm that, under the same ceramic filler ratio and process conditions, after replacing the magnesium-aluminum-silicon glass of this invention with CaO-P2O5 glass (F1 vs A2, F2 vs A3), the coefficient of thermal expansion deteriorates sharply from about 3.0~3.5 ppm / K to 6.0~6.2 ppm / K, and the flexural strength drops sharply from 260~270 MPa to 130~150 MPa. MPa, which fully verifies the mechanism described in this specification—that is, other glass systems, due to the lack of ionic composition that matches the lattice of cordierite and spodumene, cannot form an effective induced crystallization layer at the interface. Instead, they may precipitate impurity phases due to interface reaction mismatch, which destroys the intrinsic low expansion network of the filler. This, in turn, proves that there is an irreplaceable chemical compatibility and synergistic effect between the magnesium aluminum silicon glass and the specific ternary ceramic filler in this invention.

[0036] Although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

[0037] Therefore, the above description is only a preferred embodiment of this application and is not intended to limit the scope of this application; that is, all equivalent modifications made in accordance with the scope of the claims of this application shall be within the protection scope of the claims of this application.

Claims

1. A low-expansion-coefficient, high-strength magnesium-aluminum-silicon glass-ceramic composite substrate, wherein the raw material of its raw material tape includes glass powder and ceramic filler, characterized in that: The mass ratio of glass powder to ceramic filler is 34-55:25-80; the ceramic filler is composed of alumina, cordierite, and spodumene.

2. The composite ceramic substrate according to claim 1, characterized in that, The glass powder is prepared from the following raw materials in the following mass percentages: SiO2 45-55%; Al2O3 12~19%; MgO 9-15%; B2O3 12~15%; Li2O 3%~7%; ZnO 0~6%; La2O3 or Y2O3 0.3%~5%.

3. The composite ceramic substrate according to claim 1, characterized in that, The alumina accounts for 2.9% to 5.2% of the total mass of the ceramic filler, the cordierite accounts for 30.9% to 49.0% of the total mass of the ceramic filler, and the spodumene accounts for 11.2% to 15.2% of the total mass of the ceramic filler.

4. The composite ceramic substrate according to claim 1, characterized in that, The raw material tape also includes an organic casting system, the amount of which is 77% to 85% of the total mass of glass powder and ceramic filler.

5. The composite ceramic substrate according to claim 1, characterized in that, The organic casting system is at least one of a dual-solvent system, a dispersant, a binder, and a plasticizer.

6. The composite ceramic substrate according to claim 5, characterized in that, The dual-solvent system consists of ethanol and isopropanol in a mass ratio of 1:(1.2 to 1.6).

7. The composite ceramic substrate according to claim 5, characterized in that, The dispersant is selected from castor oil, polyacrylamide, or a combination thereof; the binder is polyvinyl butyral; and the plasticizer is dibutyl phthalate or its equivalent.

8. The composite ceramic substrate according to claim 5, characterized in that, The mass ratio of the dual solvent system, dispersant, binder and plasticizer is (40-70): (3-8): (6-18): (6-15).

9. The composite ceramic substrate according to claim 1, characterized in that, Its average coefficient of thermal expansion is 3.0~3.6ppm / K in the range of room temperature to 400℃, and its flexural strength is ≥260MPa.

10. A method for preparing a composite ceramic substrate as described in any one of claims 1-9, characterized in that, Includes the following steps: The glass powder is obtained by melting, quenching, crushing, and grinding the raw materials. The glass powder is mixed with ceramic filler and organic casting system to form a slurry, which is then cast, stacked, and printed with precious metal conductors to obtain a multi-layer green body. The multilayer green body is co-fired at 850~950℃ to obtain the low-expansion coefficient, high-strength magnesium-aluminum-silicon glass composite ceramic substrate.